Building Resilient Banking Sectors in the Caucasus and Central Asia - Vera Martin, Mercedes (Departmental Papers; Departmental Paper, 2018)
External shocks since 2014-lower oil prices and slower growth in key trading partners-have put financial sectors, mainly banks, in the eight Caucasus and Central Asia (CCA) countries under increased stress. Even before the shocks, CCA banking sectors were not at full strength. Asset quality was generally weak, due in part to shortcomings in regulation, supervision, and governance. The economies were highly dollarized. Business practices were affected by lack of competition and, in most countries, connected lending, which undermined banking sector health. Shortcomings in financial regulation and supervision allowed the unsound banking practices to remain unaddressed. The external shocks exacerbated in these underlying vulnerabilities. Strains in CCA banking sectors intensified as liquidity tightened, asset quality deteriorated, and banks became undercapitalized. These challenges have required public intervention in some cases.